Analisis Etos Kerja Guru dalam Melaksanakan Tugas di Sekolah Dasar - Habibah Siregar; Zul Azmi (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study aims to describe the work ethic of teachers in carrying out tasks in elementary schools. The research method used is descriptive qualitative research method, with pre-field, field, and data analysis steps. The data sources who are the key people are all 18 teachers of SDN 007 Tambusai, consisting of 5 male teachers and 13 female teachers. The data collection technique used is observation. The research instrument used was the teacher's work ethic analysis sheet and the teacher's task implementation observation sheet. The data analysis technique was carried out using qualitative data analysis techniques. The results showed that the discipline and responsibility of teachers in carrying out daily tasks were in the high category. The conclusion of this research is the work ethic of teachers in carrying out tasks in elementary schools is in the high category. The principal's attention is needed to be able to give awards to teachers who have a high work ethic. It is necessary to pay attention to the work ethic of the teachers so that it can be maintained and can be improved in the future. For teachers who have a low work ethic score, continuous coaching and mentoring is needed in order to improve their work ethic which can directly improve the discipline and responsibility of their students.